Violent Victorians: popular entertainment in nineteenth-century London - Crone, Rosalind (Manchester Univ. Press, 2012)
We are often told that the Victorians were far less violent than their forbears: over the course of the nineteenth century, violent sports were mostly outlawed, violent crime, including homicide, notably declined, and punishments were hidden from public view within prison walls. They were also much more respectable, and actively sought orderly, uplifting, domestic and refined pastimes. Yet these were the very same people who celebrated the exceptionally violent careers of anti-heroes such as the brutal puppet Punch and the murderous barber Sweeney Todd. By drawing attention to the wide range of gruesome, bloody and confronting amusements patronised by ordinary Londoners this book challenges our understanding of Victorian society and culture. From the turn of the nineteenth century, graphic, yet orderly, 're-enactments' of high level violence flourished in travelling entertainments, penny broadsides, popular theatres, cheap instalment fiction and Sunday newspapers